Addressing Hunger Through the Lens of the Informal Economy in Developing Countries - Reuveni, Saada (Technium Social Sciences Journal, 2025)
This study investigates the relationship between informal economies and food security in developing countries, focusing on how informal markets and smallholder farmers contribute to food accessibility while also facing systemic vulnerabilities. A cross-sectional quantitative design was applied to a dataset of 23 countries across Africa, Asia, and Latin America, assessing correlations between informal employment and the Global Food Security Index (GFSI). Complementary case studies from diverse regions illustrate real-world challenges and adaptive strategies within informal food systems. Statistical analysis revealed a significant negative association between high levels of informal employment and lower GFSI scores, with R² = 0.45 and a Pearson correlation coefficient of 0.67 (p < 0.01). Case studies highlighted how infrastructure gaps, income volatility, and climate vulnerability reduce food security, but also demonstrated positive outcomes where interventions - such as mobile-based market platforms, women-led cooperatives, and microfinance initiatives-have strengthened resilience. The findings emphasize that informal markets, while critical to daily food access, remain highly vulnerable without institutional support. Policies that integrate informal actors into national strategies, expand financial inclusion, and invest in climate-smart infrastructure are essential. Bridging formal and informal systems is necessary to achieve sustainable, inclusive food security.